2006
DOI: 10.1124/jpet.106.101188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Original Dual Thromboxane A2 Modulators as Antiangiogenic Agents

Abstract: Angiogenesis is a promising target for the therapy of several diseases including cancer. This study was undertaken to characterize the antiangiogenic properties of a series of original dual thromboxane A 2 (TXA 2 ) inhibitors derived from torasemide, a marketed loop diuretic with TXA 2 antagonistic properties, by evaluating their effects on human endothelial cell migration, adhesion, and viability in vitro, as well as in the ex vivo rat aortic ring assay. All drugs tested exhibited a marked affinity toward hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The eicosanoids are derived from 20-carbon (termed 'eicosa') essential fatty acids containing three, four or five double bonds [34]. The omega-6 family of eicosanoids consists of the well-known prostanoids, leukotrienes and epoxygenases [35], while the newer, omega-3 family of eicosanoids includes the eicosapentaenoic acid (EPA)-and docosahexaenoic acid (DHA)-derived resolvins and protectins [36].…”
Section: Arachidonic Acid Metabolism: Generation and Classification Omentioning
confidence: 99%
“…The eicosanoids are derived from 20-carbon (termed 'eicosa') essential fatty acids containing three, four or five double bonds [34]. The omega-6 family of eicosanoids consists of the well-known prostanoids, leukotrienes and epoxygenases [35], while the newer, omega-3 family of eicosanoids includes the eicosapentaenoic acid (EPA)-and docosahexaenoic acid (DHA)-derived resolvins and protectins [36].…”
Section: Arachidonic Acid Metabolism: Generation and Classification Omentioning
confidence: 99%
“…The PI3K-specific inhibitor, wortmannin, was purchased from Sigma Chemical Co. (St Louis, MO, USA). The concentrations of all chemicals used were based on the product datasheets and previous publications (Daniel et al, 1999;de Leval et al, 2006;Aronov et al, 2007;Li et al, 2007;Wei et al, 2007;Cailleteau et al, 2008;Moussa et al, 2008a, b), and they were proven to be optimal in the present study. Dimethylsulfoxide, an organic solvent, was used in the treatment with different drugs.…”
Section: Chemicals and Drug Treatmentmentioning
confidence: 99%
“…Dual TXS/TP inhibitors have been shown to dose-dependantly inhibit endothelial cell migration in chemotaxis assays. In addition, pretreatment of endothelial cells with these original dual inhibitors significantly attenuated TP agonist-induced intracellular Ca 2+ pool mobilization, suggesting a mechanistic link between TXS/TP inhibition and reduced endothelial cell migration [158].…”
mentioning
confidence: 94%
“…Ozagrel is therefore an interesting pharmacological tool to evaluate the role of thromboxane synthase and TXA 2 production in both physiologic and pathologic states [175,179]. A recent report has demonstrated that dual TXA 2 inhibitors (which display dual inhibitory activity of both TXS and TP) exhibit anti-angiogenic properties in human endothelial cells, suggesting that this pathway may be an attractive target for anti-angiogenic/anti-cancer therapies [158]. In addition to this, TP antagonists have been shown to sensitize non-small cell lung cancer cells to cisplatin in several studies.…”
mentioning
confidence: 99%